Data Warehouse and its tools - Mrđa Bojan; Soleša Dragan (Ekonomija: teorija i praksa, 2023)
As the battle for every and even the smallest piece of the pile on the market is great, a growing number of companies are finding solutions to improve their business as much as possible. One of the solutions is Data Warehouse and OLAP, that is, their tools, which gives managers or users the ability to access, with minimal effort, the very important data that is important to them for the business. This paper presents data analysis on concrete examples of the Belgrade Academy, where the mentioned tools were used with the aim of improving the quality of teaching.